Enhancing solubility of low grade phosphorus minerals for their utilization as plant nutrients - Sharma, Gulshan Kumar; Dev, Rahul; Dayal, Devi; Singh, Traloki (Indian Farming, 2018)
Rock phosphate is one of the important sources for phosphatic fertilizer, but solubility of rock phosphate is low. In general it was observed that due to phosphorusfixation availability of phosphorus to crop plants is always low, causes phosphorus deficiency to crop plants. Solubility of rock phosphate can be increased by following several measures like using biological organism (VAM, vermicompost) with soil, nano-technological approaches and several coated fertilizers like polymer-coated watersoluble phosphorus fertilizers. Nanoclay polymer composite containing nutrients (N-P2O5) was found to be more effective than urea-DAP mixture in relation to P.